Planning for sustainable urban mobility in Italy. Insights from Palermo and Cagliari - Angiello, Gennaro (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of a continuous updating of emerging topics concerning relationships among urban planning, mobility and environment, through a collection of short scientific papers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban Practices section aims at producing, analyzing and reporting data on recent and relevant policies in the urban domain. The present note in particular reports on the recent initiatives undertaken by two major Southern Italian cities to foster sustainable mobility: Palermo and Cagliari. To this aim, the note briefly introduces the legal background and current developments of the Sustainable Urban Mobility Plan (SUMP), a framework developed by the European Commission to support local administrations in developing holistic urban mobility strategies. This is followed by (i) an overview of the mobility situations in Palermo and Cagliari and by (ii) an analysis of the objectives, the strategies and the measures set in their respective SUMPs.